REPRESENTASI MAKNA PERSAHABATAN DALAM FILM "LASKAR PELANGI" : Analisis Semiotika Roland Barthes - Indah Ayu Anduwenny, - (2019)
The film Laskar Pelangi is inspired by the true story of the struggle of the Belitung children who want to go to school, a strong determination to learn and teacher service amid limitations. Therefore, it is very important to know the purpose of the research is to know the meaning of friendship from the Laskar Pelangi film so that people can find out films that educate and through this film, can inspire generations of future generations. The research method used, Semiotics seeks to find signs that have meaning, and know the sign systems such as language, motion, music, images and so on. The concept of research, namely film, is a living image, also called a movie. This research uses qualitative research methods. Where the researcher will explain the semiotic analysis using the theory of Roland Barthes. And using scene per scene in the film. The results of the study found that there were only 4 secene which contained friendship meanings from 10 scenes which the authors analyzed. The conclusion resulted in the meaning of denotation, connotation, meaning of the myth implied in the meaning of friendship of this film. Then it can be seen that the film Rainbow Pelangi has a positive message meaning to educate and educate the nation's children. Through the meaning of the message from the Laskar Pelangi film, we can recognize that as the next generation of the nation we must continue to learn, do not easily give up with difficulties and as educators are the characters who want to serve the Indonesian people. And for the people of Indonesia must be able to choose which films are worth watching and those that are not. Author's advice for producers, directors and film production houses. Make a film that educates the nation so that our nation has an extraordinary generatio